Flexible Automation in Porcelain Edge Polishing Using Machine Vision. (2016) - Hosseininia, S.J.; Khalili, K.; Emam, S.M.
Abstract: The first step in producing glazed porcelain dishes is molding of raw material granules. Then, the biscuit of the dishes is formed. This process is performed by press machines under high pressures. Dishes formed have usually burrs around the edges. To improve flexibility and increase product quality, robots are employed for dish polishing process for which the exact position of the dish is required. This paper deals with the problem in a real world manufacturing line. Machine vision technology and image processing techniques are employed, implemented and integrated with the current robotic system to detect the pose (position and orientation) of biscuits, hence guiding the robot arm to perform its polishing operation at correct and most efficient pose. The system and algorithms have been developed. The development has been done for two representative sample dishes of circular and rectangular shapes, both of which were developed and tested successfully.